The Sepsis in Obstetrics Score. Issue 3 (September 2015) - Albright, C.M.; Ali, T.N.; Lopes, V.; Rouse, D.J.; Anderson, B.L.
<x xml:space="preserve">Abstract</x> (Am J Obstet Gynecol. 2014;211:39.e1–39e8)